2017
DOI: 10.18632/oncotarget.16185
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol induces paraptosis of leukemia cells through p38 mitogen activated protein kinase signaling pathway

Abstract: Xanthohumol as a natural polyphenol demonstrates an anticancer activity, but its underlying mechanism remains unclear. In this study, we showed that xanthohumol (XN) induces paraptosis of leukemia cells. The paraptosis is one cell death which is characterized by dilation of the endoplasmic reticulum and/or mitochondria. The results demonstrated that XN treatment significantly inhibited cell proliferation and triggered extensive cytoplasmic vacuolation of HL-60 leukemia cells, but it did not cause the cleavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Similarly, the autophagy inhibition was also observed in XN-treated A431 cell lines [42]. It has been reported that autophagy was inhibited by XN at the fusion of autophagosomes with lysosomes step in HL-60 cells [43]. Thus, autophagy was not the degradation way of XN-induced BCR-ABL degradation.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, the autophagy inhibition was also observed in XN-treated A431 cell lines [42]. It has been reported that autophagy was inhibited by XN at the fusion of autophagosomes with lysosomes step in HL-60 cells [43]. Thus, autophagy was not the degradation way of XN-induced BCR-ABL degradation.…”
Section: Discussionmentioning
confidence: 85%
“…It has been reported that cytoplasmic vacuolation induced by paraptosis is due to ER stress [ 16 , 21 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Paraptosis is a type of nonapoptotic cell death characterized by dilation of the endoplasmic reticulum (ER) and/or mitochondria. Although the molecular mechanism of paraptosis is not well elucidated, studies have revealed that paraptosis is independent of the caspase signaling cascade and may involve activation of the mitogen-activated protein kinase (MAPK) pathway [ 15 , 16 ]. The ER stress markers Bip and Chop were found to be elevated in paraptosis [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…During apoptosis, intracellular contents are not released and potentially harmful inflammatory responses are prevented. Apoptotic cell death is characterized by a DNA fragmentation into 180–200 pb nucleosomal units [ 17 ] and at the molecular level the apoptotic way can also be monitored trough the Annexin V/PI assay [ 57 ]. The DNA fragmentation assay was only able to detect apoptosis in HL60 exposed to highest concentrations of “Light Green” zucchini epicarp.…”
Section: Discussionmentioning
confidence: 99%